2002
DOI: 10.1046/j.1365-2591.2002.00468.x
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of a new apex locator: an in vitro study

Abstract: Kaufman AY, Keila S, Yoshpe M. Accuracy of a new apex locator: an in vitro study. International Endodontic Journal , 35 , 186-192, 2002. Aim The purpose of this study was to test in an in vitro model the accuracy of a Bingo 1020 electronic apex locator, to compare the results to those of a well known apex locator, Root ZX, as well as to those of the radiographic method of tooth length determination. Methodology A total of 120 extracted teeth, preserved in Thymol solution and kept refrigerated, was used fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
109
6
7

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(130 citation statements)
references
References 11 publications
8
109
6
7
Order By: Relevance
“…9,16,17 Dentaport ZX, Root ZX mini, Elements Diagnostic Unit&Apex Locator ve Raypex 5 EAB cihazların kök kanal boyunu tespit etmede güvenilirlik-lerinin kıyaslandığı bir çalışmada, Root ZX mini cihazı-nın gerçek çalışma boyutunu başarılı olarak tespit edebildiği bulunmuştur 9 . Bingo 1020 ve Root ZX EAB cihazlarının kullanıldığı bir çalışmada ise kök kanal boyu tespitinde elektronik ölçümler radyografilerden daha gü-venilir bulunmuştur.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…9,16,17 Dentaport ZX, Root ZX mini, Elements Diagnostic Unit&Apex Locator ve Raypex 5 EAB cihazların kök kanal boyunu tespit etmede güvenilirlik-lerinin kıyaslandığı bir çalışmada, Root ZX mini cihazı-nın gerçek çalışma boyutunu başarılı olarak tespit edebildiği bulunmuştur 9 . Bingo 1020 ve Root ZX EAB cihazlarının kullanıldığı bir çalışmada ise kök kanal boyu tespitinde elektronik ölçümler radyografilerden daha gü-venilir bulunmuştur.…”
Section: Discussionunclassified
“…Bingo 1020 ve Root ZX EAB cihazlarının kullanıldığı bir çalışmada ise kök kanal boyu tespitinde elektronik ölçümler radyografilerden daha gü-venilir bulunmuştur. 16 Tek köklü insan dişinde yapılan in vivo çalışmada Propex II cihazının kök kanal boyu tespitinde güvenilirliği araştırılmış ve cihazın etkili olduğu belirtilmiştir. 17 Propex II ve standart radyografik yönte-min kıyaslandığı bir çalışmada, Propex II'nin daha gü-venilir olduğu görülmüş; radyografik yöntemin doğruluğu %76.6 olarak bulunurken Propex II cihazının doğruluğu %86.6 olarak bulunmuştur.…”
Section: Discussionunclassified
“…In vitro studies showed high efficacy of EAL in primary teeth, providing better quality in endodontic deciduous treatment 4,[11][12][13] . Thus, the aim of this in vitro study was to compare the performance of two electronic apex locators, Propex II and Root ZX, and digital radiograph in primary molars.…”
Section: Introductionmentioning
confidence: 99%
“…Kaufman et al 15 concluded that presence of CHX did not affect the accuracy of electronic apex locators. Fan et al 15 encountered, in dry tubes that the accuracy of Root ZX was 75 to 91.7% within ± 0.5 mm and 100% within ± 1.0 mm, whereas in tubes filled with electrolyte, the accuracy of the Root ZX decreased as tubule diameter increased.…”
mentioning
confidence: 99%
“…Fan et al 15 encountered, in dry tubes that the accuracy of Root ZX was 75 to 91.7% within ± 0.5 mm and 100% within ± 1.0 mm, whereas in tubes filled with electrolyte, the accuracy of the Root ZX decreased as tubule diameter increased. However, the results of this study are in accordance with their findings.…”
mentioning
confidence: 99%